2011
DOI: 10.1016/j.jcrs.2010.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of effective lens position using a method independent of preoperative keratometry readings

Abstract: Purpose To evaluate the validity of a keratometry-independent method of estimating effective lens position (ELP) prior to phacoemulsification cataract surgery. Setting Institute of Eye Surgery, Whitfield Clinic, Waterford, Ireland Methods The anterior chamber diameter (AGm) and corneal height (Hm) in 95 eyes (95 patients) scheduled for cataract surgery were measured with a rotating Scheimpflug camera. Hm and AGm were used to estimate the ELP in a keratometry-independent method (using the SRK/T [ELPrs] and Holl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Pereira et al [27] also found that the distance between the iris and IOL was increased over a period after cataract surgery, and the same result was observed by OCT in the anterior segment [31]. Although it is difficult to estimate the ELP after cataract surgery, researchers are still seeking a solution [9, 32, 33]. A recent study showed that the preoperative ACD demonstrated the greatest influence on the IOL calculation formulas, and the postoperative change in the ACD correlated significantly with errors of third generation formulas according to a simulated ACD [34].…”
Section: Discussionmentioning
confidence: 94%
“…Pereira et al [27] also found that the distance between the iris and IOL was increased over a period after cataract surgery, and the same result was observed by OCT in the anterior segment [31]. Although it is difficult to estimate the ELP after cataract surgery, researchers are still seeking a solution [9, 32, 33]. A recent study showed that the preoperative ACD demonstrated the greatest influence on the IOL calculation formulas, and the postoperative change in the ACD correlated significantly with errors of third generation formulas according to a simulated ACD [34].…”
Section: Discussionmentioning
confidence: 94%
“…ELP remains a challenge to predict even with IOLs placed in the capsular bag. 7,8 ELP in the Yamane technique is likely dependent on a number of different variables such as distance of sclerotomies from the limbus, white-to-white distance, length of haptic cauterized, and any shortening of haptic tips beyond the initial cautery than those with standard in-the-bag placed IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Because of challenges in accurately assessing corneal power in postrefractive surgery patients, we investigated a keratometry-independent (K-independent) approach to the prediction of postoperative ACD as well. Our method outperformed a previously reported method for K-independent prediction of ACD 19 and may be applicable in new methods for IOL power calculation in patients with prior refractive surgery. Performance of this K-independent model was not significantly different for patients with or without prior refractive surgery, indicating its applicability to the postrefractive surgery population.…”
Section: Discussionmentioning
confidence: 57%